2008
DOI: 10.54207/bsmps1000-2008-comt61
|View full text |Cite
|
Sign up to set email alerts
|

Plant diversity in alpine pasture of Talra wildlife sanctuary of district Shimla, Himachal Pradesh

Abstract: Studies to evaluate the plant diversity and growth forms in alpine pasture of Talra Wildlife Sanctuary of District Shimla, Himachal Pradesh were carried out during August, 2003. Total 75 species of plant, comprising of 7 grasses, 4 sedges, 4 leguminous forbs and 60 non-leguminous forbs were recorded from the area. On the basis of Importance Value Index (IVI). Sibbaldia cuneata O. Ktze., was found to be the dominant species followed by Geum elatum Wall ex D. Don., Ligularia amplexicaulis DC., Primula denticula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The dominance of these families in the alpine pasture was due to their phytogeographic origin and specific niches adapted for the alpine climates. Similar findings were reported by several workers while conducted study in alpine pastures and other high altitude forest ecosystems such as Gaur et al (2005) Santvan (1993); Verma et al (2008); Verma and Chauhan (2022). The overgrazing does not only alter their botanical compositions but also result in to the degradation of pasture.…”
Section: Medicinal and Threatened Plantssupporting
confidence: 86%
See 2 more Smart Citations
“…The dominance of these families in the alpine pasture was due to their phytogeographic origin and specific niches adapted for the alpine climates. Similar findings were reported by several workers while conducted study in alpine pastures and other high altitude forest ecosystems such as Gaur et al (2005) Santvan (1993); Verma et al (2008); Verma and Chauhan (2022). The overgrazing does not only alter their botanical compositions but also result in to the degradation of pasture.…”
Section: Medicinal and Threatened Plantssupporting
confidence: 86%
“…In the present study, tall forbs varied from 22.22% to 24.19%, short forbs varied from 61.11% to 61.29% and cushion spreading forbs varied from 14.52% to 16.67% were observed during the year in different season. Similar findings were reported by different workers while conducted the study in alpine pasture such as Ram et al (1988) observed 17% were tall forbs, 36% short forbs and 27% cushion and spreading forbs, Santvan (1993) for the alpine pasture near Rahla, reported 22.5% tall forbs, 45.0% short forbs and 32.5% cushion and spreading forbs, Pandey et al (1999) observed the tall forbs contribute 27.4%, short forbs 39.2%, cushion and spreading forbs 25.2%, grasses and sedges 5.9%, Verma et al (2008) reported 29.33% tall forbs, 54.66% short forbs and 16% cushion and spreading forbs whereas Verma and Chauhan (2022) reported 41.46% tall forbs, 52.44% short forbs and 6.10% cushion and spreading forbs. The short forbs usually have hairy leaves which protect them against frost condition.…”
Section: Medicinal and Threatened Plantsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the present study, tall forbs varied from Verma and Chauhan (2022). The overgrazing does not only alter their botanical compositions but also cause degradation of pasture.…”
Section: Resultsmentioning
confidence: 58%
“…The sanctuary vegetation is de ned by the guidelines and requirements of Pine and Oak forests at lower elevations and conifer forests composed of Cedrus deodara, Abies pindrow, Acer spp., and Picea smithiana, interspersed with dwarf Rhododendron species at higher elevations (Mahabal, 2000). Verma et al (2008) conducted a similar study, recording 75 plant species from the TWLS alpine pastures, including 7 types of grasses, 4 sedges, 4 leguminous forbs, and 60 non-leguminous forbs. There are 61 species of birds in total, spread over 19 families, of which 32 species (52.5%) are endemic residents of the Himalayan habitat and 13 species (21.3%) are seasonal migrant species (Mahabal, 2000).…”
Section: Study Areamentioning
confidence: 99%